Phenethyl Ester of Gallic Acid Ameliorates Experimental Autoimmune Encephalomyelitis - Goran Stegnjaić; Antonios D. Tsiailanis; Milica Lazarević; Vasileios K. Gkalpinos; Neda Djedovic; Thomas Antoniou; Suzana Stanisavljević; Mirjana Dimitrijević; Miljana Momčilović; Đorđe Miljković; Andreas G. Tzakos; Bojan Jevtić (Molecules, 2022)
Gallic acid is a phenolic acid present in various plants, nuts, and fruits. It is well known for its anti-oxidative and anti-inflammatory properties. The phenethyl ester of gallic acid (PEGA) was synthesized with the aim of increasing the bioavailability of gallic acid, and thus its pharmacological potential. Here, the effects of PEGA on encephalitogenic cells were examined, and PEGA was found to modulate the inflammatory activities of T cells and macrophages/microglia. Specifically, PEGA reduced the release of interleukin (IL)-17 and interferon (IFN)-γ from T cells, as well as NO, and IL-6 from macrophages/microglia. Importantly, PEGA ameliorated experimental autoimmune encephalomyelitis, an animal model of chronic inflammatory disease of the central nervous system (CNS)—multiple sclerosis. Thus, PEGA is a potent anti-inflammatory compound with a perspective to be further explored in the context of CNS autoimmunity and other chronic inflammatory disorders.